How to contact focus groups - Hadjigeorgiou, Eleni (My University, 2019)
Εργαστήριο με θέμα «How to contact focus groups» στα πλαίσια του Ευρωπαϊκό ερευνητικό πρόγραμμα “Baby Buddy Forward”.
Keywords: Focus groups